The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7554/elife.28270
|View full text |Cite
|
Sign up to set email alerts
|

Native KCC2 interactome reveals PACSIN1 as a critical regulator of synaptic inhibition

Abstract: KCC2 is a neuron-specific K+-Cl– cotransporter essential for establishing the Cl- gradient required for hyperpolarizing inhibition in the central nervous system (CNS). KCC2 is highly localized to excitatory synapses where it regulates spine morphogenesis and AMPA receptor confinement. Aberrant KCC2 function contributes to human neurological disorders including epilepsy and neuropathic pain. Using functional proteomics, we identified the KCC2-interactome in the mouse brain to determine KCC2-protein interactions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 137 publications
3
39
3
Order By: Relevance
“…The specific gene networks altered by adolescent THC involved regulation of actin dynamics at excitatory synapses and dendritic spines, which recapitulates on a molecular level the morphological alterations . Notable genes with enhanced THC sensitivity included pyramidal-enriched Pacsin1, as well as Clu and Snap25, which are implicated in psychiatric diseases, such as schizophrenia and mood disorders (Wang et al, 2015;Pouget et al, 2016;Mahadevan et al, 2017). Intriguingly, the coordinated expression of genes altered by THC across development overlap with PFC gene expression networks dysregulated in humans with schizophrenia .…”
Section: Neurodevelopmental Thc Impacts the Epigenetic Landscape Relementioning
confidence: 99%
“…The specific gene networks altered by adolescent THC involved regulation of actin dynamics at excitatory synapses and dendritic spines, which recapitulates on a molecular level the morphological alterations . Notable genes with enhanced THC sensitivity included pyramidal-enriched Pacsin1, as well as Clu and Snap25, which are implicated in psychiatric diseases, such as schizophrenia and mood disorders (Wang et al, 2015;Pouget et al, 2016;Mahadevan et al, 2017). Intriguingly, the coordinated expression of genes altered by THC across development overlap with PFC gene expression networks dysregulated in humans with schizophrenia .…”
Section: Neurodevelopmental Thc Impacts the Epigenetic Landscape Relementioning
confidence: 99%
“…), we have previously demonstrated that changes in E GABA can be detected using whole‐cell recordings (Ormond and Woodin, , Ormond and Woodin, , Takkala and Woodin, , Mahadevan et al . ). The use of the whole‐cell technique was necessary in the present study as a result of the longer‐term nature of the recordings, which required the washing‐in and ‐out of pharmacological agents, and the need to include a pharmacological agent in the recording pipette.…”
Section: Resultsmentioning
confidence: 98%
“…KCC2 has also been shown to physically interact with several excitatory receptors and proteins (Mahadevan et al . ), including the GluK2 subunit of kainate receptors (KARs) (Mahadevan et al . ), and the KAR auxiliary subunit Neto‐2 (Ivakine et al .…”
Section: Introductionmentioning
confidence: 99%
“…KCC2 interacts with a variety of transmembrane as well as intracellular partners, including postsynaptic receptors 44,45,46 , actin-related proteins 34,35,36 and others involved in protein trafficking and recycling 37 . Although these interactions are most often considered with regard to KCC2 expression or function, they also influence the function of KCC2 partners.…”
Section: Discussionmentioning
confidence: 99%
“…Through interactions with multiple transmembrane and intracellular partners, KCC2 was shown to regulate dendritic spine morphology 33,34 and actin cytoskeleton 35,36 , as well as the strength and long-term plasticity of glutamatergic synapses 33,35 . Recent functional proteomics data revealed additional putative KCC2 partners, including some involved in the recycling and trafficking of various transmembrane proteins and receptors 37 . Those may then either influence KCC2 function or, conversely, be regulated by KCC2.…”
Section: Introductionmentioning
confidence: 99%